2000
DOI: 10.2343/geochemj.34.207
|View full text |Cite
|
Sign up to set email alerts
|

The major, trace and rare earth element geochemistry of glauconites from the early Cretaceous Kurnub Group of Jordan.

Abstract: The major, trace and REE geochemistry of glauconites (as members of the trioctahedral micas) from the early Cretaceous Kurnub Group of Jordan are discussed. The investigated glauconites, with 7.1 to 9.2% K 2 O, are ranked as evolved to highly evolved as defined by Odin and Matter (1981). Al 2 O 3 contents show a significant inverse relationship with K 2 O and Fe 2 O 3 .The trace element contents show a broad range of variation in contrast to the major elements and a consistent relationship with major elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
0
26
1
Order By: Relevance
“…10C) and between K 2 O and CaO (Fig. 10D), in contrast to Jarrar et al (2000) who found good correlation for these oxides. Higher Fe 2 O 3 (total) content distinguishes the CSF peloids from the DFF peloids in the scatter plots (Fig.…”
Section: Chorhat Sandstonecontrasting
confidence: 39%
See 2 more Smart Citations
“…10C) and between K 2 O and CaO (Fig. 10D), in contrast to Jarrar et al (2000) who found good correlation for these oxides. Higher Fe 2 O 3 (total) content distinguishes the CSF peloids from the DFF peloids in the scatter plots (Fig.…”
Section: Chorhat Sandstonecontrasting
confidence: 39%
“…As per AIPEA definition, glauconite is an Fe-rich dioctahedral mica (Jarrar et al, 2000). Mn 2+ is negligible in the minerals and is not represented in the formula.…”
Section: Chorhat Sandstonementioning
confidence: 99%
See 1 more Smart Citation
“…Gruner 46 reported that glauconite is similar to the layer structures of mica, kaolinites vermiculite or chlorite (clay family). Jarrar et al 47 described its structure as sheet-like, while Odin and Matter 48 , as well as Odin 49 designated it as a dark green pelletal structure. Hence, due to its supposed clay mineral content and structure, the real relative permittivity of glauconite is a little less than that of shale.…”
Section: Discussionmentioning
confidence: 99%
“…The Lusi mud is a shale rock type that contains highly SiO 2 , Al 2 O 3 and K 2 O. This type of rocks is usually more enriched in the REE [22,23] compared to arenaceous rock types [24,25]. So, this may be the case that the LREE is found to be abundant within the Lusi mud [26][27][28].…”
Section: Ree Content and Clay Structurementioning
confidence: 97%